KONSEP RELASI LAFáº’ DAN MAâ€˜NÄ€ DALAM PERSPEKTIF â€˜ABDUL QÄ€HIR AL-JURJÄ€NÄª DAN IMPLIKASINYA TERHADAP PENAFSIRAN - Fikri, M Kamalul (Lajnah Pentashihan Mushaf Al-Qur'an, 2018)
One of the study objects in Arabic study is related to the issue of (word) and ma'naÂ (meaning). The lafáº“ and ma'naÂ studies are actually not only seriously studied by 'Abdul QÄhir al-JurjÄnÄ« (d. 471 H/ 1078 CE). In general, there are at least two groups in linguistic studies, namely the group that emphasizes mostly on pronunciation and another one is supported group of meaning. According to al-JurjÃ„Âni, a lafáº“ is a sign, an attribute for ma'naÂ. Lafáº“ becomes part of language which is not placed to show ma'naÂ for itself, but to be collected from one another so that the contents are known. The existence of a lafáº“ is certainly be preceded by ma'naÂ, while ma'naÂ in the view of al-JurjÄnÄ« is the intended idea or purpose. This article reveals and understands al-JurjÄnÄ«'s theory of the relationship between lafáº“ and ma'naÂ and their implications to the interpretation of the Qur'an. This research is a qualitative research by using the main references of two phenomenal works of al-Jurjani, namely DalÄil al-Iâ€™jÄz and AsrÄr al-BalÄgah.